Efficacy and mechanism of Jiedu Tongluo Tiaogan Formula in treating type 2 diabetes mellitus combined with non-alcoholic fatty liver disease: Study protocol for a parallel-armed, randomized controlled trial - Xu, Jinghan; Piao, Chunli; Qu, Yue; Liu, Tianjiao; Peng, Yuting; Li, Qi; Zhao, Xiaohua; Li, Pei; Wu, Xuemin; Fan, Yawen; Chen, Binqin; Yang, Jie (Frontiers in Pharmacology, 2022)
Background: The incidence of type 2 diabetic mellitus(T2DM) combined with non-alcoholic fatty liver disease (NAFLD) is rising over the years, and this comorbid disease significantly increases the probability of cirrhosis, liver cancer and even a fatal outcome compared to the disease alone. The multi-targeted, holistic treatment efficacy characteristics of Traditional Chinese Medicine (TCM) play a vital role in the treatment of T2DM combined with NAFLD. Jiedu Tongluo Tiaogan Formula (JTTF), a formula constructed based on TCM theory, is widely used in clinical treatment, while its effectiveness in lowering glucose, regulating lipids, improving insulin resistance and its pathways of action have been demonstrated in previous studies. However, the mechanism of this formula has not been investigated from a metabolomics perspective, and there is a lack of high-quality clinical studies on T2DM combined with NAFLD. Therefore, we conducted a clinical trial to investigate the clinical efficacy, safety and possible pathways of JTTF in the treatment of T2DM combined with NAFLD by combining metabolomics techniques. Methods: This study is designed as a clinical trial. A total of 98 participants will be recruited and randomly assigned to the treatment group (JTTF + conventional basic treatment) and control group (conventional basic treatment) in a 1:1 ratio. Both groups will receive the same lifestyle interventions and last 12 weeks. The change in visceral fat area will be set as the primary outcome, and the secondary outcome will be the changes in ultrasound steatosis grade, Fibrosis 4 Score(FIB-4), metabolic parameters, anthropometric parameters, subcutaneous fat area and the total score on TCM Syndromes Efficacy Score Scale. In addition, serum and urine samples collected at baseline and at the end of 12 weeks of treatment will be sequentially tested for untargeted and targeted metabolomics. Discussion: This study will evaluate the efficacy and safety of JTTF, as well as investigate the differential metabolites and possible mechanisms of JTTF treating T2DM combined with NAFLD. We hypothesize that patients will benefit from JTTF. The results of this study will provide strong evidence for the clinical use of JTTF in the treatment of the disease and the possibility of mechanistic exploration.